Identifikasi Risiko Pencemaran Air Limbah Domestik - Leonard, Franita; Wahyuni; Hasanuddin (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Atma Jaya Makassar, 2024)
Water has a very important role for the environmental ecosystem, water is very necessary to fulfill the sustainability of living creatures and the natural surroundings, but also as a potential source of renewable energy in sustainable development. This research aims to identify the risk of environmental pollution that occurs in the discharge of domestic wastewater. Water samples were taken directly using the grab sampling method using a water sampler in accordance with SNI. The samples were taken to a KAN-accredited laboratory for analysis. The parameters analyzed include pH, Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) parameters. After obtaining the results of the analysis, data analysis was carried out to determine the results of the research using descriptive and quantitative analysis methods. The analysis results for the pH parameter obtained a value of 6.2, the BOD parameter was 12.7 mg/L, and the COD parameter was 24.41 mg/L. Based on the results of the pH analysis, and in the domestic wastewater tested, it can be concluded that the analysis results for the pH, BOD and COD parameters meet the quality standards based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.68/Menlhk/Setjen/Kum.1/ 8/2016 Concerning Domestic Wastewater Quality Standards. Keywords: Domestic Wastewater, pH, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Quality Standards